1992
DOI: 10.1002/j.1556-6676.1992.tb02191.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Illness and Subscription to Ellis's Irrational Beliefs

Abstract: Research has shown a generally positive correlation between a person's propensity for illness and certain psychosocial variables. This study investigated the relationship between age, sex, and degree of subscription to each of Ellis's 10 irrational beliefs and frequency and type of illness. Participants were 122 adults who were assessed on the Irrational Beliefs Test and an illness questionnaire. Participants' scores on both instruments were analyzed using a canonical correlation analysis. There was a statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…He found that female students experience significantly higher dysfunctional attitudes than male students. Similarly, Lichterberg and Johnson [49] conducted study on adult sample and reported that female scored higher on competence, achievement and approval.…”
Section: Discussionmentioning
confidence: 93%
“…He found that female students experience significantly higher dysfunctional attitudes than male students. Similarly, Lichterberg and Johnson [49] conducted study on adult sample and reported that female scored higher on competence, achievement and approval.…”
Section: Discussionmentioning
confidence: 93%
“…This study suggests that irrational beliefs maybe a risk factor for cardiovascular diseases. Indeed, irrational beliefs have been shown to affect physical health, with irrational beliefs positively related to eating disorders ( Möller and Bothma, 2001 ) such as bulimia ( Phillips et al, 1997 ), more severe asthma symptoms ( Silverglade et al, 1994 ), and a higher frequency of chronic illnesses ( Lichtenberg et al, 1992 ). Indeed, irrational beliefs are also positively related to type-A coronary-prone behavior, where individuals are highly motivated and competitive, but feel near constant time pressure, and have high hostility and anger ( Friedman, 1977 ).…”
Section: Moving the Area Forwardmentioning
confidence: 99%
“…The impact of maladaptive beliefs on physical health has been examined in several studies. Maladaptive beliefs have been associated with more physical symptoms (Howlett, 1994), and have been found to mediate the impact of stress and hostility on physical health (Lichtenberg et al, 1992; VanderVoort, 2006) as well as to affect caregivers’ well-being in a negative way (Stebbins and Pakenham, 2001). Furthermore, maladaptive health beliefs have been related to worse regimen adherence in adults with diabetes (Christensen et al, 1999), poor decision making in HIV+ individuals (Benotsch et al, 2004), higher levels of health anxiety (Fulton et al, 2011) and weaker internal health locus of control (Christensen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%